2019
DOI: 10.1136/tsaco-2019-000307
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic blockade for attenuation of catecholamine surge after traumatic brain injury: a randomized pilot trial

Abstract: BackgroundBeta-blockers have been proven in multiple studies to be beneficial in patients with traumatic brain injury. Few prospective studies have verified this and no randomized controlled trials. Additionally, most studies do not titrate the dose of beta-blockers to therapeutic effect. We hypothesize that propranolol titrated to effect will confer a survival benefit in patients with traumatic brain injury.MethodsA randomized controlled pilot trial was performed during a 24-month period. Patients with trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…1,9 While few interventions have shown to improve mortality in this population, recent studies suggest that BB may be of benefit during the initial hospitalization. [4][5][6][7][8] The index study demonstrated that the odds of mortality were reduced by 77% in multivariable analysis in the cohort of patients that received propranolol. 4 A prospective randomized pilot trial examining propranolol in TBI also showed a protective effect of this medication as the propranolol group had a higher end-study GCS (11.7 vs 8.9; P = .044) despite that study not being powered to show differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,9 While few interventions have shown to improve mortality in this population, recent studies suggest that BB may be of benefit during the initial hospitalization. [4][5][6][7][8] The index study demonstrated that the odds of mortality were reduced by 77% in multivariable analysis in the cohort of patients that received propranolol. 4 A prospective randomized pilot trial examining propranolol in TBI also showed a protective effect of this medication as the propranolol group had a higher end-study GCS (11.7 vs 8.9; P = .044) despite that study not being powered to show differences.…”
Section: Discussionmentioning
confidence: 99%
“…4 A prospective randomized pilot trial examining propranolol in TBI also showed a protective effect of this medication as the propranolol group had a higher end-study GCS (11.7 vs 8.9; P = .044) despite that study not being powered to show differences. 6 Few studies in the trauma literature address long-term outcomes of TBI patients after discharge from the initial hospitalization. Interestingly, while propranolol was found to be protective in the index study that did not hold true after discharge in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[133][134][135][136][137][138][139][140] There have been only two RCTs evaluating the impact of adrenergic blockade on TBI outcomes. 141,142 Schroeppel et al 141 performed a pilot RCT comparing propranolol (starting dose of 20 mg in every 8 hours) to placebo whose primary outcomes were in-hospital mortality and plasma/urine catecholamine levels. Though underpowered to detect a mortality benefit, it did find trends toward higher GCS at 14 days or hospital discharge in the treatment arm, (which was not the primary outcome).…”
Section: Adrenergic Blockade In Pshmentioning
confidence: 99%
“…Though underpowered to detect a mortality benefit, it did find trends toward higher GCS at 14 days or hospital discharge in the treatment arm, (which was not the primary outcome). 141 Our group performed the decreasing adrenergic or sympathetic hyperactivity (DASH) after severe TBI study, 142 an RCT evaluating the α-agonist clonidine in combination with the nonselective α-blocker propranolol given parenterally compared with placebo. The primary outcome was ventilator-free days, and secondary outcomes included plasma and urine catecholamine levels, delirium/coma-free days, ICU/hospital length of stay, PSH CFS scale, arousal and sedation, GCS, as well as long-term outcomes such as global cognition, functional status, and quality of life.…”
Section: Adrenergic Blockade In Pshmentioning
confidence: 99%